2001
DOI: 10.1002/1099-095x(200103)12:2<103::aid-env447>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the diffuse fraction of global solar radiation on a horizontal surface

Abstract: For various applications it is necessary to know not only global solar radiation values\ but also the di}use and beam components[ Because often only global values are available\ there have been several models developed to establish correlations between the di}use fraction and various predictors[ These typically include the clearness index\ but also may include the solar angle\ temperature and humidity[ The clearness index is the proportion of extraterrestrial radiation reaching a location\ where the extraterre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 0 publications
0
49
0
4
Order By: Relevance
“…To account for the presence of clouds, three decomposition models were implemented: Erbs et al (1982), Reindl et al (1990) , andBoland et al (2001). The procedure described here is in line with Helbig et al (2010).…”
Section: The Shortwave Radiation Correction For Cloudy Sky Dec-mod'smentioning
confidence: 99%
“…To account for the presence of clouds, three decomposition models were implemented: Erbs et al (1982), Reindl et al (1990) , andBoland et al (2001). The procedure described here is in line with Helbig et al (2010).…”
Section: The Shortwave Radiation Correction For Cloudy Sky Dec-mod'smentioning
confidence: 99%
“…Boland et al developed a model in order to determine the influence that the smoothing due to the use of hourly data (instead of 15-minute data) has on the results. The model was carried out utilizing data from Australian locations, to explain some of the substantial scatter by adding apparent solar time as a predictor, which showed to be significantly better than solar altitude [11].…”
Section: Introductionmentioning
confidence: 99%
“…The soft computing technique has the capacity of accepting many input parameters for a particular model which is not possible applying regression technique and this strengthens its reliability. Therefore, applying soft computing techniques compared to regression techniques according to previous studies offers greater accuracy with prediction error in a range (less than 20 %) and could be very good in terms of diffuse solar radiation prediction as more and more soft computing approaches are demanded in the domains of renewable energy resource prediction [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Boland and Scott [18] determined the comparison between the empirical models and a fuzzy logic based model to estimate hourly diffuse solar radiation in some locations of Australia. The results revealed that coefficients of determination recorded for the fuzzy logic model are comparable, and in most cases more suitable than those of empirical models.…”
mentioning
confidence: 99%